PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA GURU SDN SEKAR PUTIH KABUPATEN GRESIK - Mustofa Bisri; Waras Waras (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
The Influence of Competence and Job Satisfaction on the Performance of Teachers at Sekar Putih Sdn Bhd, Gresik Regency. This study aims to: (1) To describe competence, job satisfaction and teacher performance at SDN Sekar Putih, Gresik Regency, (2) To test and analyze the effect of work competence on teacher performance at SDN Sekar Putih, Gresik Regency, (3) To test and analyze the influence job satisfaction on the performance of Guru Sdn Sekar Putih (4) To test and analyze the effect of competency and job satisfaction simultaneously on the performance of Guru Sdn Sekar Putih, Gresik Regency. This research is a type of quantitative research using a sample of 33 people with the saturated sample method. Collecting research data using a questionnaire. This study uses SPSS. The results of this study indicate that competence has a positive and significant effect on teachers of SD Negeri Sekar Putih, Gresik Regency, job satisfaction has a positive and significant effect on teachers of SD Negeri Sekar Putih, Gresik regency, competency and job satisfaction have a positive and significant effect simultaneously on teachers of SD Negeri Sekar Putih district. Gresik.